Analisis Kepemilikan Atribut Soft Skills Mahasiswa Program Studi Pendidikan Ekonomi FKIP Univesitas Jambi - Zuhri Saputra Hutabarat (Universitas Batanghari Jambi, 2019)
This study aim to find out the soft skill attributes of students, soft skills based on devices from 2015 to 2017, soft skills based on gender, and soft skills based on student origin. The method uses a survey research approach with a population of all Economics Education FKIP Jambi University students in the class of 2015, 2016 and 2017. The respondents as sampled was 180 people. As for the results: 1) The soft skills attributes that the students have overall are very good with a Relative Frequency of 63.91%. 2) The ability of student soft skills from class, 2015, 2016 and 2017 is very good with an absolute frequency of 36 and a relative frequency of 69.23% and Soft Skills Ability Student devices have increased from 2015 to 2017. 3) Student's Soft Skills based on gender were found that women were higher than men with very good average abilities with results of count 25 for men and women count 122. 4) Soft Skills students based on the origin of the village and the city, the results of the analysis obtained F count coefficient of 0.218 with a rejection rate of 64.10% thus there is no difference in the average ability of students soft skills from the city and from the village. Suggestions in this study before using soft skills assessment instruments regarding student interpersonal relations, we must first study and understand the instructions for assessing instruments, assessment procedures and the core of the assessment in each rubric.